Um arcabouço para a construção de aplicações baseadas em componentes sobre uma plataforma de nuvem computacional para serviços de computação de alto desempenho - Silva, Jefferson de Carvalho (2016)
Developing High Performance Computing applications (HPC), which optimally access the available computing resources in a higher level of abstraction, is a challenge for many scientists. To address this problem, we present a proposal of a component computing cloud called HPC Shelf, where HPC applications perform and SAFe framework, a front-end aimed to create applications in HPC Shelf and the author's main contribution. SAFe is based on Scientific Workflows Management Systems (SWMS) projects and it allows the specification of computational solutions formed by components to solve problems specified by the expert user through a high level interface. For that purpose, it implements SAFeSWL, an architectural and orchestration description language for describing scientific worflows. Compared with other SWMS alternatives, besides rid expert users from concerns about the construction of parallel and efficient computational solutions from the components offered by the cloud, SAFe integrates itself to a system of contextual contracts which is aligned to a system of dynamic discovery (resolution) of components. In addition, SAFeSWL allows explicit control of life cycle stages (resolution, deployment, instantiation and execution) of components through embedded operators, aimed at optimizing the use of cloud resources and minimize the overall execution cost of computational solutions (workflows). Montage and Map/Reduce are the case studies that have been applied for demonstration, evaluation and validation of the particular features of SAFe in building HPC applications aimed to the HPC Shelf platform.